The Transcendental Paradigm Of The Development Of Legal Law - Absori Absori; Sigit Sapto Nugroho (Law Doctoral Program Universitas Muhammadiyah Surakarta, 2019)
Purpose of the study: This article aims to formulate (1) epistemology jurisprudence has the positivistic level, (2) jurisprudence epistemology has transcendental paradigm, and (3) epistemology of the development of prophetic jurisprudence. Methodology: This research uses library research by conducting research and data analysis and then they use it using knowledge, especially jurisprudence with transcendental values. Main Findings: The base of epistemological positivistic jurisprudence that is objective, empirical and rational which are supported by systematic, procedural and formal models result in its development has lost essential elements, namely spiritual values, so that modern society has a crisis in defining the meaning of life in the world. Applications of this study: The base of transcendental legal science understands people and their life in an intact form (holistic), not merely material nature but also their souls. The development of the prophetic law is intended as a guidance for human life to achieve happiness in the world and in the hereafter, because the prophetic law can not be fragmented between the physical body (formal) and transcendental values. Novelty/Originality of this study: The paradigm of the transcendental epistemology of legal science emphasizes in the integration approaches between sciences and values in various views